Iodine L-edge XAFS study of linear polyiodide chains in amylose and alpha-cyclodextrin - Konishi, T (Journal of synchrotron radiation, 2001)
We performed iodine L edge XAFS measurements on blue-black amylose-iodine complex to obtain information about the electronic and geometrical structures of polyiodide chain included in amylose helix. Measurements were also carried out on crystalline alpha-cyclodextrin-iodine complex (alpha-cyclodextrin)2 x Cd0.5 x I5 x 27H2O, in which the polyiodide chain is known to consist of I(5)- unit. It was found that the XANES spectra of these complexes have similar line shapes except for some minor differences, indicating that there are close similarities in the nature of polyiodide chains in these complexes. Besides their similarity, difference in the intensity of the peak at the L1 absorption edge was observed. Its implication for the electronic and geometrical structures is also discussed